2020
DOI: 10.3390/ijerph17165802
|View full text |Cite
|
Sign up to set email alerts
|

Household Air Pollution and Angina Pectoris in Low- and Middle-Income Countries: Cross-Sectional Evidence from the World Health Survey 2002–2003

Abstract: The evidence regarding the effects of household air pollution on angina pectoris is limited in low-and middle-income countries (LMICs). We sought to examine the association between household air pollution and angina pectoris across several countries. We analyzed data of individuals from 46 selected countries participating in the cross-sectional World Health Survey (WHS) 2002–2003. Pooled and stratified (sex, continent) logistic regression with sampling weights was used to estimate adjusted odds ratios (ORs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…A stove intervention study [60] in Peru observed reduced headache in the intervention group, those with new chimney-equipped stoves, than those with mostly open-fire stoves in the control group. Another study in multiple countries showed that higher odds of angina pectoris were observed mainly with household solid fuel use [61].…”
Section: Discussionmentioning
confidence: 99%
“…A stove intervention study [60] in Peru observed reduced headache in the intervention group, those with new chimney-equipped stoves, than those with mostly open-fire stoves in the control group. Another study in multiple countries showed that higher odds of angina pectoris were observed mainly with household solid fuel use [61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HAP is related to the risk of pain in certain parts of the body (such as the chest and back, etc.) 26,64 , and pain has also been associated with the risk of disability. Buchman et al found that in nondisabled community-dwelling older adults, the risk of disability increased with the number of reported musculoskeletal pain areas, and for each additional pain area, the risk of ADL disability increased by 20% and IADL disability increased by 10% 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epidemiological studies reported that long-term exposure to HAP from solid fuel use not only affects outcomes related to disability but also impacts physical and psychological outcomes, such as pain and depression. For example, the World Health Survey (WHS) linked HAP caused by the use of solid fuels to angina pectoris and increased the incidence of eye soreness and headaches in a Guatemalan population 26,27 . In addition, a controlled trial reported an association between HAP and depression in 1756 women in India and indicated that the degree of depression among women exposed to HAP was 23.4% higher than that among those not exposed to HAP 28 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Angina, also known as angina pectoris, is a medical term used in the field of internal medicine to describe chest pain or discomfort induced by insufficient blood and oxygen supply to the heart [1] . As an important subtype of ischemic heart disease (IHD), angina manifests a wide range of symptoms related to ischemia and could substantially jeopardize the health status of patients or even pose threats to their lives [2] .…”
Section: Introductionmentioning
confidence: 99%